Righteous : an IQ novel - Ide, Joe (Ide, Joe. IQ novel., 2017)
"Isaiah Quintabe has, against many odds, built a proper life for himself: a respected detective in his hometown of East Long Beach, a well-kept home, a growing library, and even a rehabilitated horse-sized pit bull (courtesy of his previous client). But something is wrong: the death of his older brother nearly a decade ago has sent him down a dark path, one that he's never truly been able to escape. RIGHTEOUS is the story of Isaiah's investigation of his brother's death, a quest that will lead him to his greatest adversary, a man who may be IQ's own Moriarty. RIGHTEOUS is also the story of Sarita, Isaiah's older brother's girlfriend, for whom Isaiah feels a lasting, troubling love. Sarita's younger sister, an erratic DJ and gambling addict, has gone missing in Las Vegas, with a frightening bookie, Chinese Triad gangsters, and her own deadbeat boyfriend hot on her tail. On the case once more with Dodson, Isaiah's fast-talking, don't-call-me-a-sidekick partner, mayhem is sure to ensue. With gun battles, carchases, and twice as many mental puzzles as before, RIGHTEOUS is a rollicking, ingenious, and thrilling roller coaster ride. It swerves from the streets of South Central to the hotels of Beverly Hills, from the casinos and massage parlors of Las Vegas to the mountains of the desert Southwest. IQ is back, and he's badder than ever"--